![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
b) Thay \(f\left(-1\right)\)vào \(y=f\left(x\right)=-1,5x\)ta có:
\(-1,5.\left(-1\right)=1,5\)
Vậy \(f\left(1\right)=1,5\)
Thay \(f\left(1\right)\)vào \(y=f\left(x\right)=-1,5x\)ta có:
\(-1,5.1=-1,5\)
Vậy \(f\left(1\right)=-1,5\)
Thay \(f\left(-2\right)\)vào \(y=f\left(x\right)=-1,5x\)ta có:
\(-1,5.\left(-2\right)=3\)
Vậy \(f\left(-2\right)=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : \(f\left(1\right)=-\frac{1}{2}.1=-\frac{1}{2}\)
\(f\left(-2\right)=-\frac{1}{2}\left(-2\right)=1\)
\(f\left(-1\right)=-\frac{1}{2}\left(-1\right)=\frac{1}{2}\)
\(f\left(0\right)=-\frac{1}{2}0=0\)
Ta có : \(y=-\frac{1}{2}x=-1\Leftrightarrow x=2\)
\(y=-\frac{1}{2}x=0\Leftrightarrow x=0\)
\(y=-\frac{1}{2}x=2\Leftrightarrow x=-4\)
f(-3)=-6